Sewing Service Order Information Web-Based (a Case Study at Iendandy Modiste) - Sri Murni; Mizanul Ahkam; Devi Mulia Sari; Ichsan; Elfisa (LPPM Politeknik Aceh Selatan, 2023)
Ordering sewing services is a crucial fashion industry process requiring efficiency and easy customer access. It aims to make customer easier to place orders and improve operational efficiency for sewing service providers. Through the implementation of this system, customers can easily choose and order sewing services according to their needs through a responsive and easy-to-use web platform. Sewing service providers will also benefit from this system by improving the order process, managing orders more organized, and increasing customer satisfaction. The design of this system is built using PHP and MySQL programming languages as databases. Workflow design on this system uses DFD (Data Flow Diagram) and ERD (Entity Relationship Diagram). With this system, it can help Iendandy Modiste in increasing bookings.